The Effect of Acute Organophosphate Intoxication on Female Rat Hippocampus Cornu Ammonis Region Pyramidal Neuron Numbers, Biochemistry and Morphology - Bas, Orhan; Cankaya, Soner; Enginyurt, Ozgur; Aslan, Ali; Uydu, Huseyin Avni; Odaci, Ersan; Gul, Tuba (Elsevier, 2019)
Background: The most commonly used insecticides and pesticides worldwide are organophosphate compounds, chemicals that irreversibly inhibit the cholinesterase enzyme. Acute intoxication with cholinesterase inhibitors is known to cause permanent effects on both the human and rat brains. Aim: To investigate the effect of acute organophosphate intoxication on hippocampus morphology, biochemistry, and pyramidal neuron numbers in female rats. Methods: Twenty-one rats were randomly divided into three groups. The control group received normal nutrition and underwent no procedures. The sham group received intraperitoneal physiological serum, while the experimental group received intraperitoneal 0.8 g/kg fenthion. Rats were sacrificed 24 h after these procedures. The brains were removed and divided in two halves medially, with one side being kept in 10% neutral formalin. After fixation procedures, tissues were embedded in blocks, sliced, and stained. A neuron count was then performed for the hippocampus. The other hippocampus was homogenized and used for biochemical procedures. Results: Hippocampus sections from rats in the experimental group exhibited swelling and loss of shape in pyramidal cells, while no changes were observed in the control or sham groups. The number of neurons in the experimental group was lower than in the control and sham groups. Biochemical analysis revealed higher MDA and GSH values in the experimental group compared to the control and sham groups. Conclusion: Our results show increased apoptotic neurodegeneration of cells in the cornu ammonis region of the hippocampus and changes in biochemical values in rats with acute organophosphate exposure.
Keywords: Organophosphate; Fenthion; Hippocampus; Stereology; Rat